Drivers of intraspecific genetic differentiation of a wheat’s wild relative Leymus racemosus: roles of isolation by distance and environmental factors - Zhang, Zhuo; Shi, Xiaojun; Tian, Haowen; Tan, Dunyan (Frontiers in Plant Science, 2025)
Understanding how environmental heterogeneity shape genetic structure is fundamental to unraveling adaptive evolution and guiding conservation practices. Northern Xinjiang, characterized by its unique geological history and complex ecosystems, provides an ideal system to explore species-environment interactions. The riverine system, topographic relief, arid climate, and other factors have collectively shaped the genetic structure and adaptive trajectories of regional species. Leymus racemosus, a species well adapted to drought conditions, is primarily distributed along the Irtysh River basin. This study aims to examine the relative contributions of geographic distance, environmental factors, and their interactions to the genetic divergence of L. racemosus. Genomic SNP data from 135 individuals across 27 populations were generated through Double-digest restriction site-associated DNA (dd-RAD) sequencing. Population structure analyses employing ADMIXTURE, PCA, and phylogenetics revealed distinct genetic clusters. Gradient forest (GF) and redundancy analysis (RDA) were conducted to assess the environmental effects on genetic variation. Results suggest that low population genetic diversity and population structure analyses identified two evolutionarily distinct lineages (A and U). The divergence time between these two lineages can be traced back to the mid-to-late Last Glacial Period (0.0295 million years ago), a timescale that is highly consistent with the repeated glacial advances and retreats driven by the intense climatic fluctuations of the Quaternary Ice Age. Environmental association analyses (EAA) revealed significant correlations between allelic variation and climatic gradients, particularly with annual precipitation (bio12) and minimum temperature in the coldest month (bio6). Analyses of isolation by distance (IBD) and isolation by environment (IBE) further underscore the role of geographic distance and environment distance in the genetic differentiation of L. racemosus. This study reveals the pattern of genetic structure of L. racemosus populations and its association with environmental factors, contributing to the development of targeted strategies for species conservation and ecological restoration.